The Role of Needs Analysis in Designing Relevant Learning Outcomes for EFL Curriculum: Literature Review - Meilyani, Annisa; Rinalgi, Dimitria; Nandha, Marisa Shermia; Qamariah, Zaitun (Datokarama English Education Journal, 2025)
Designing an effective English as a Foreign Language (EFL) curriculum necessitates a comprehensive understanding of learners’ linguistic, academic, and sociocultural needs. This qualitative literature review critically examines the role of needs analysis in shaping relevant and context-sensitive learning outcomes for EFL programs. Drawing upon peer-reviewed studies published between 2015 and 2025, this study applies content analysis to identify recurring themes and gaps in the literature. The findings converge on three interrelated insights: (1) the imperative of constructing learner-centered and contextualized curricula; (2) the detrimental impact of omitting systematic needs analysis, often resulting in decontextualized and ineffective learning outcomes; and (3) the transformative role of participatory needs analysis involving multiple stakeholders. The review reveals that when needs analysis is consistently implemented, it enhances curricular relevance, learner motivation, and instructional alignment. Conversely, underutilization—especially in centralized or under-resourced systems—undermines curriculum effectiveness. The study advocates for an epistemological shift in curriculum development: reconceptualizing needs analysis as a continuous, dialogic process rather than a preliminary task. The paper concludes by proposing institutional strategies for integrating technology, stakeholder feedback, and reflective practice into the curriculum development cycle. These findings offer critical implications for educators, curriculum designers, and policymakers aiming to foster adaptive, equitable, and learner-responsive EFL education.